2020
DOI: 10.1172/jci.insight.129070
|View full text |Cite
|
Sign up to set email alerts
|

ELA/APELA precursor cleaved by furin displays tumor suppressor function in renal cell carcinoma through mTORC1 activation

Abstract: Renal cell carcinoma (RCC) is one of the most common malignancies worldwide, accounting for 140,000 cancer-related deaths and 330,000 new cases a year (1). Various environmental and daily life risk factors for RCC are well established, including hypertension, obesity, and several chronic kidney diseases. In adults, malignant kidney tumors mainly arise from the renal parenchyma and renal pelvis (2). RCC is classified into clear cell RCC (ccRCC), papillary RCC, and chromophobe RCC subtypes (2). Accounting for up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…An increasing number of studies have identified a wide range of protein precursors in breast cancer cells of which the cleavage and activity are inhibited by furin repression [ 10 , 17 , 31 , 33 , 52 ]. These studies highlight the important role for the cleavage of these protein precursors in breast cancer development and progression and reveal that their cleavage inhibition results in tumor cells proliferation, invasion, and survival inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have identified a wide range of protein precursors in breast cancer cells of which the cleavage and activity are inhibited by furin repression [ 10 , 17 , 31 , 33 , 52 ]. These studies highlight the important role for the cleavage of these protein precursors in breast cancer development and progression and reveal that their cleavage inhibition results in tumor cells proliferation, invasion, and survival inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The wound-healing assay was conducted as previously reported [ 52 ]. Briefly, control and ppFurin-expressing cells were seeded into 6-well plates at 5 × 105/well and grown in growth media until 90–100% confluency.…”
Section: Methodsmentioning
confidence: 99%
“…Furin has been implicated in regulating multiple oncogenic pathways like MAPK and PI3K signaling [ 11 , 50 ]. Our finding here supports the idea that inhibition of MAPK and PI3K signaling by interfering with maturation of proIGF1R and proIR contributes to inhibiting tumor growth by enhancing apoptosis in the PyMT-induced TNBC mouse model ( Figure 4 C,D).…”
Section: Discussionmentioning
confidence: 99%
“…Recent years saw a significant increase in the studies focusing on the association between Apela and cancer. Soulet et al found that Apela was usually expressed by epithelial cells while expression of APJ could be found in various kidney cells (77). Expression of Aplea was reduced in the main kidney cancer subtypes, namely, clear cell, papillary, and chromophobe RCC.…”
Section: Role Of Apela In Cancersmentioning
confidence: 99%